Kemampuan Petani dalam Mengalokasikan Biaya Pada Usahatani Jahe di Desa Taro Kecamatan Tegallalang Kabupaten Gianyar - KADEK AGUS DWISAPUTRA; I WAYAN WIDYANTARA; RATNA KOMALA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2015)
ABSTRAK Farmers’ Capability in Allocating Costs in Ginger Farming in Taro Village Tegallalang Sub District Gianyar Regency. Ginger (Zingiber Oflnule) is a spice plant potential to be developed because it has a high economic value. Ginger commodity value lies at its root wand called a rhizome. The purpose of this research was to know whether farmers had been able to allocate the costs of ginger farming efficiently, to know the profits of ginger farming and the selling place of ginger. Based on the results of research in the village of Taro, the ginger farming in the village of Taro was not optimal, because the marginal costs were not equal to the average variable costs. It showed that ginger farmers in the village of Taro did not produce efficiently. Ginger farming profits were Rp 150.670.250,00 per an area (38,37 area) of arable land per planting season. The profit of ginger farming obtained, ginger farming in the village of Taro should be maintained because ginger cultivation prospect is very bright. It is centered in traditional markets, swalayan and the people market. The sales some of the farming ginger, because ginger demands are more for household needs, such as for religious ceremonies and traditional medicine. Beside the traditional is a market that is easily accessible by residents. Based on this research are advised to farmers, in order to increase production in the area of arable land is being managed by farmer without killing the plants that have the selling price of high and adjust land that is worthy to be ginger and market department store. Keyword: capability, farmers, cost, farming, ginger